2016
DOI: 10.3390/fib4010004
|View full text |Cite
|
Sign up to set email alerts
|

Experiment-Based Sensitivity Analysis of Scaled Carbon-Fiber-Reinforced Elastomeric Isolators in Bonded Applications

Abstract: Fiber-reinforced elastomeric isolators (FREIs) are a new type of elastomeric base isolation systems. Producing FREIs in the form of long laminated pads and cutting them to the required size significantly reduces the time and cost of the manufacturing process. Due to the lack of adequate information on the performance of FREIs in bonded applications, the goal of this study is to assess the performance sensitivity of 1/4-scale carbon-FREIs based on the experimental tests. The scaled carbon-FREIs are manufactured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Some research works already exist on Partially Bonded FREIs (PB-FREIs) [35][36][37][38][39], and bonded [40] or restrained FREIs [41]. In a PB-FREI, two thick steel mounting plates were bonded to portions of the outer surfaces at the top and bottom of the isolator.…”
Section: Investigated Constraint Systemmentioning
confidence: 99%
“…Some research works already exist on Partially Bonded FREIs (PB-FREIs) [35][36][37][38][39], and bonded [40] or restrained FREIs [41]. In a PB-FREI, two thick steel mounting plates were bonded to portions of the outer surfaces at the top and bottom of the isolator.…”
Section: Investigated Constraint Systemmentioning
confidence: 99%
“…Sensitivity analysis is used to investigate how the output is affected by the system's uncertainty. As a result, a sensitivity analysis is performed with assumptions on the parameters with higher uncertainty [62,90]. In this study, the following steps were adopted to carry out the sensitivity analysis:…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Besides the above researches, in order to further reduce the manufacturing cost and production difficulty of the bearings, some scholars tried to change the manufacturing method, the fiber material and the form of the bearings. Ashkezari et al (2008) studied the steel like fiber reinforced elastomeric seismic isolators by experiment; Hedayati Dezfuli and Alam (2014, 2016) used industrial glue to realize the cold bonding between carbon fiber cloth and rubber sheet; Karimzadeh Naghshineh et al (2014, 2015) studied the mechanical properties of a new type of fiber-mesh-reinforced seismic isolators; Spizzuoco et al (2014) and Losanno et al (2019b, 2020a) introduced the application of recycled rubber in fiber reinforced rubber bearings; Losanno et al (2019a, 2020b) studied mechanical properties of innovative polyester fiber reinforced elastomeric isolators; Tan et al [26] used the unsaturated polyester fiber reinforcement engineering plastic sheet that has a much larger out-of-plane stiffness than the general fiber-reinforced layer as the reinforcement layer, which further resulted in the ultimate shear deformation of the bearing reaching 300%. Wu et al (2020) found that the internal structure of the industrial fabric core conveyor belt is similar to that of the fiber reinforced rubber bearing, so they combined multiple layers of conveyor belt plates by cold bonding to form the bearings with much lower cost and simpler manufacturing process.…”
Section: Introductionmentioning
confidence: 99%